Septic shock in pediatrics: the state‐of‐the‐art - Pedro Celiny Ramos Garcia; Cristian Tedesco Tonial; Jefferson Pedro Piva (Brazilian Society of Pediatrics, 2020)
Objective: Review the main aspects of the definition, diagnosis, and management of pediatric patients with sepsis and septic shock. Source of data: A search was carried out in the MEDLINE and Embase databases. The articles were chosen according to the authors' interest, prioritizing those published in the last five years. Synthesis of data: Sepsis remains a major cause of mortality in pediatric patients. The variability of clinical presentations makes it difficult to attain a precise definition in pediatrics. Airway stabilization with adequate oxygenation and ventilation if necessary, initial volume resuscitation, antibiotic administration, and cardiovascular support are the basis of sepsis treatment. In resource‐poor settings, attention should be paid to the risks of fluid overload when administrating fluids. Administration of vasoactive drugs such as epinephrine or norepinephrine is necessary in the absence of volume response within the first hour. Follow‐up of shock treatment should adhere to targets such as restoring vital and clinical signs of shock and controlling the focus of infection. A multimodal evaluation with bedside ultrasound for management after the first hours is recommended. In refractory shock, attention should be given to situations such as cardiac tamponade, hypothyroidism, adrenal insufficiency, abdominal catastrophe, and focus of uncontrolled infection. Conclusions: The implementation of protocols and advanced technologies have reduced sepsis mortality. In resource‐poor settings, good practices such as early sepsis identification, antibiotic administration, and careful fluid infusion are the cornerstones of sepsis management. Resumo: Objetivo: Revisar os principais aspectos da definição, diagnóstico e manejo do paciente pediátrico com sepse e choque séptico. Fontes de dados: Uma pesquisa nas plataformas de dados Medline e Embase foi feita. Os artigos foram escolhidos segundo interesse dos autores, priorizaram‐se as publicações dos últimos 5 anos. Síntese dos dados: A sepse continua a ser uma causa importante de mortalidade em pacientes pediátricos. A variabilidade de apresentação clínica dificulta uma definição precisa em pediatria. A estabilização da via aérea com adequada oxigenação, e ventilação se necessário, ressuscitação volêmica inicial, administração de antibióticos e suporte cardiovascular são a base do tratamento da sepse. Em cenários de poucos recursos, deve‐se atentar para os riscos de sobrecarga hídrica na administração de fluidos. A administração de drogas vasoativas, como adrenalina ou noradrenalina, se faz necessária na ausência da resposta ao volume na primeira hora. O seguimento do tratamento do choque deve seguir alvos como restauração dos sinais vitais e clínicos de choque e controle do foco de infecção. Recomenda‐se a avaliação multimodal, com auxílio da ecografia à beira‐leito para manejo após as primeiras horas. No choque refratário, deve‐se atentar para situações como tamponamento cardíaco, hipotireoidismo, insuficiência adrenal, catástrofe abdominal e foco de infecção não controlado. Conclusões: Implantação de protocolos e avançadas tecnologias propiciou uma redução da mortalidade da sepse. Em cenários de poucos recursos, as boas práticas, como reconhecimento precoce da sepse, administração de antibióticos e cuidadosa infusão de fluidos, são os pilares do manejo da sepse. Keywords: Infection, Sepsis, Shock, Child, Mortality, Intensive Care Units, Palavras‐chave: Infecção, Sepse, Choque, Criança, Mortalidade, Unidade de Cuidados Intensivos